Role of Metabolic Stress and Exercise in Regulating Fibro/Adipogenic Progenitors - Collao, Nicolas; Farup, Jean; De Lisio, Michael (Frontiers in Cell and Developmental Biology, 2020)
Obesity is a major public health concern and is associated with decreased muscle quality (i.e. strength, metabolism). Muscle from obese adults is characterized by increases in fatty, fibrotic tissue that decreases the force producing capacity of muscle and impairs glucose disposal. Fibro/adipogenic progenitors (FAPs) are muscle resident, multipotent stromal cells that are responsible for muscle fibro/fatty tissue accumulation. Additionally, they are indirectly involved in muscle adaptation through their promotion of myogenic (muscle-forming) satellite cell proliferation and differentiation. In conditions similar to obesity that are characterized by chronic muscle degeneration, FAP dysfunction has been shown to be responsible for increased fibro/fatty tissue accumulation in skeletal muscle, and impaired satellite cell function. The role of metabolic stress in regulating FAP differentiation and paracrine function in skeletal muscle is just beginning to be unraveled. Thus, the present review aims to summarize the recent literature on the role of metabolic stress in regulating FAP differentiation and paracrine function in skeletal muscle, and the mechanisms responsible for these effects. Furthermore, we will review the role of physical activity in reversing or ameliorating the detrimental effects of obesity on FAP function.